Tilapia (Oreochromis niloticus) trait preferences by women and men farmers in Jessore and Mymensingh districts of Bangladesh - Meher, Mamta; Mekkawy, Wagdy; McDougall, Cynthia; Benzie, John (Elsevier, 2023)
Research reporting user trait preferences for fish, particularly in relation to guiding genetic improvement programs are rare, even in tilapia where demand for genetically improved fish has underpinned the expansion of fish farming. The present study investigated gender-disaggregated trait preferences for tilapia by fish farmers in Bangladesh using open-ended questions and stated choice experiment, using 1000minds software. Men and women from smallholder fish farming households shared preferences for some traits of tilapia, but differed in others or in the strength of preference, mostly influenced by the prevailing yet constraining social norms around gender-appropriate work for fish farming, mobility and household responsibilities. Feed intake was the shared top priority for ‘improvement’ for both genders, and confirms the relevance of ongoing efforts in breeding program. However, the importance given to body shape by these users was revealed although more work will be needed to understand the precise requirements given potentially contradictory rankings within and between genders. A number of priority traits reacted to as freshness and taste could be easily improved with better farm management practices and/or improvement in value chain practices.